Hubungan Lama Penggunaan Laptop dengan Keluhan Neck Pain pada Mahasiswa Diploma Tiga Keperawatan Universitas Abulyatama Aceh - Ferlita Ferlita; Fauziah Fauziah; Mansuriza Mansuriza (Lembaga Pengembangan Kinerja Dosen, 2025)
Research at Diponegoro University found that 66.7% of 63 respondents experienced neck pain due to using a laptop for more than 4 hours. Prolonged laptop use can negatively impact health from an ergonomic perspective, as the recommended maximum usage is 2 hours per day. However, students often maintain non-ergonomic positions for extended periods. This study aimed to determine the relationship between laptop use and neck pain among Diploma Three Nursing Students at Abulyatama University, Aceh. The research utilized an analytical, cross-sectional design, with a population of 556 students and a sample of 85 students, selected through purposive random sampling. The research was conducted at Abulyatama University from May 15 to June 2, 2025, and data was collected using a questionnaire with a Numeric Rating Scale. Analysis involved both univariate and bivariate methods using the Chi-Square test. The results showed that among 85 respondents, 44 (95.7%) experienced moderate pain, 8 (40.0%) had mild pain, and 8 (42.1%) reported severe pain. Statistical analysis indicated a significant correlation (p=0.000) between laptop use and neck pain. In conclusion, there is a strong relationship between laptop use and complaints of neck pain among university students. The research is expected to raise student awareness about the health risks associated with prolonged and improper laptop use, encourage better posture, and serve as a reference about limiting laptop use and improving ergonomics.